Monitoring fatigue crack growth using nonlinear ultrasonic phased array imaging. (10th April 2017) - Cheng, Jingwei; Potter, Jack N; Croxford, Anthony J; Drinkwater, Bruce W
Abstract: Nonlinear imaging techniques have recently emerged which have the potential to detect material degradation and challenging defects, such as closed cracks. This paper describes an investigation into the performance of nonlinear ultrasonic imaging (NUI) for the monitoring of the early stages of fatigue crack growth. This technique, in conjunction with conventional array imaging, is applied to the periodic monitoring of steel compact tension specimens subjected to high cycle fatigue loading. The detection limits of these techniques are investigated. Their abilities to localise and detect small cracks are further quantified with the aid of micrography. The results suggest that NUI is more sensitive than conventional ultrasonic imaging to the microscale changes occurring at the early stages of failure, i.e. detectability starts c. 15% of fatigue life. In addition to early detection, the potential for NUI to deliver accurate sizing of fatigue cracks and monitor crack propagation is also presented.